3(3m-3)=5(3m-3)

Simple and best practice solution for 3(3m-3)=5(3m-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(3m-3)=5(3m-3) equation:



3(3m-3)=5(3m-3)
We move all terms to the left:
3(3m-3)-(5(3m-3))=0
We multiply parentheses
9m-(5(3m-3))-9=0
We calculate terms in parentheses: -(5(3m-3)), so:
5(3m-3)
We multiply parentheses
15m-15
Back to the equation:
-(15m-15)
We get rid of parentheses
9m-15m+15-9=0
We add all the numbers together, and all the variables
-6m+6=0
We move all terms containing m to the left, all other terms to the right
-6m=-6
m=-6/-6
m=1

See similar equations:

| 3x+2/3=7x+8 | | 2/5n+6=13 | | g3+4=2 | | 10-8x=3x | | 3(x-4)=3(x+10) | | 45-5x=-5x+55 | | 95+(2x+5)=180 | | 25=5/w-10 | | x+2/5=3/2 | | x+3/2=2/5 | | 5v+8=22 | | 8(x-1)=-2(x-41 | | 3x-13=41 | | 3x+3(x+2)+1=6x+7 | | 2(c-18)=-22 | | y2+15=26 | | 9=1/3x+1 | | -(a+9)=4(3-1) | | 3/7=x-2-6 | | (0.12y+y)=4400 | | -3(n+7)=6 | | s=57+(77)(15) | | 4+2.2h=−3.74 | | 16v-45=525 | | -30(c-957)=-450 | | z/6+3=-57 | | -4m+2=10 | | 7/x+9=7/12 | | 47.9-x=-21.6 | | 17(w-955)=204 | | 0.2x-0.5(2x-1)=-0.3(x+2) | | 24w+35=371 |

Equations solver categories